Aldosterone Jeopardizes Myocardial Insulin and β-Adrenergic Receptor Signaling via G Protein-Coupled Receptor Kinase 2 - Cannavo, Alessandro; Marzano, Federica; Elia, Andrea; Liccardo, Daniela; Bencivenga, Leonardo; Gambino, Giuseppina; Perna, Claudia; Rapacciuolo, Antonio; Cittadini, Antonio; Ferrara, Nicola; Paolocci, Nazareno; Koch, Walter J.; et al. (Frontiers in Pharmacology, 2019)
Hyperaldosteronism alters cardiac function, inducing adverse left ventricle (LV) remodeling either via increased fibrosis deposition, mitochondrial dysfunction, or both. These harmful effects are due, at least in part, to the activation of the G protein-coupled receptor kinase 2 (GRK2). In this context, we have previously reported that this kinase dysregulates both β-adrenergic receptor (βAR) and insulin (Ins) signaling. Yet, whether aldosterone modulates cardiac Ins sensitivity and βAR function remains untested. Nor is it clear whether GRK2 has a role in this modulation, downstream of aldosterone. Here, we show in vitro, in 3T3 cells, that aldosterone impaired insulin signaling, increasing the negative phosphorylation of insulin receptor substrate 1 (ser307pIRS1) and reducing the activity of Akt. Similarly, aldosterone prevented the activation of extracellular signal-regulated kinase (ERK) and the production of cyclic adenosine 3′,5′-monophosphate (cAMP) in response to the β1/β2AR agonist, isoproterenol. Of note, all of these effects were sizably reduced in the presence of GRK2-inhibitor CMPD101. Next, in wild-type (WT) mice undergoing chronic infusion of aldosterone, we observed a marked GRK2 upregulation that was paralleled by a substantial β1AR downregulation and augmented ser307pIRS1 levels. Importantly, in keeping with the current in vitro data, we found that aldosterone effects were wholly abolished in cardiac-specific GRK2-knockout mice. Finally, in WT mice that underwent 4-week myocardial infarction (MI), we observed a substantial deterioration of cardiac function and increased LV dilation and fibrosis deposition. At the molecular level, these effects were associated with a significant upregulation of cardiac GRK2 protein expression, along with a marked β1AR downregulation and increased ser307pIRS1 levels. Treating MI mice with spironolactone prevented adverse aldosterone effects, blocking GRK2 upregulation, and thus leading to a marked reduction in cardiac ser307pIRS1 levels while rescuing β1AR expression. Our study reveals that GRK2 activity is a critical player downstream of the aldosterone signaling pathway; therefore, inhibiting this kinase is an attractive strategy to prevent the cardiac structural disarray and dysfunction that accompany any clinical condition accompanied by hyperaldosteronism.